PERFORMANCE OF THE GUNUNG JAYA AGRARIAN REFORM VILLAGE, SOUTHEAST SULAWESI: A STUDY OF THE CHALLENGES OF ACHIEVING AGRARIAN REFORM GOALS - Nur Hidayani Alimuddin; Jusafri (Universitas Bengkulu, 2024)
Agrarian Reform Village (ARV) is a pilot project in various Indonesian regions to prepare areas for the small-scale implementation of agrarian reform, including asset management and access management. The aim of this study is to know the perfomance of Agrarian Reform Village (ARV) in Gunung Jaya Village, Dangia District, Southeast Sulawesi and to know the challenges faced in implementing the program to achieve the goals of agrarian reform. Its social legal research consists of primary data obtained directly from the field or research location and elaborated with secondary data that is already available in the form of legal materials and relevant to the research topic. This study found that the performance of Gunung Jaya Agrarian Reform Village, which includes land redistribution, economic community empowerment, and reform access, was not optimal enough. There are several inhibiting factors that become challenges for the optimalization of the program, such as the planting process, maintenance, and capital problems. The local government and the Ministry of Agrarian Affairs and Spatial Planning, as organizers, continue to strive to resolve these obstacles for the implementation of the agrarian reform village in following year to realize the achievements of agrarian reform.Keywords: Village; Reform; Agrarian.